Photobiomodulation for the Prevention of Chemotherapy-Induced Peripheral Neuropathy: Randomized Clinical Trial Protocol - Fernandes, Maíra Carneiro; Fabro, Erica Alves Nogueira; Costa, Rejane Medeiros; Torres, Daniele Medeiros; de Aguiar, Suzana Sales; Lenzi, Juliana; de Alcântara, Rodrigo Ramos; Bergmann, Anke (Mastology, 2025)
Chemotherapy applied as a breast cancer treatment may result in chemotherapy-induced peripheral neuropathy (CIPN) as a side effect, encompassing varying degrees of toxicity, according to the employed drug’s pharmacokinetics, administration period, and cumulative dose. In this sense, photobiomodulation employing LASER or LED comprises a safe and non-pharmacological low-cost resource that has been widely studied for the mitigation and even resolution of various oncological comorbidities. The objective of this study is to evaluate the effectiveness of photobiomodulation employing a LED Therapeutic Display (LTD) in the prevention of lower limb CIPN in breast cancer female patients undergoing chemotherapy. Methods: This study encompasses a randomized double-blind superiority clinical trial including women aged 18 and over presenting breast cancer stages I to IIIC with indication for curative treatment applying neoadjuvant or adjuvant chemotherapy. Following recruitment, patients will be allocated into three groups: two intervention groups, which will undergo infrared and red LTD (A) and infrared, red, and violet LTD (B), and a control group (C), which will apply LTD with no light emission. The LTD applications will be conducted at home for 20 minutes daily on each plantar region, until the last day of chemotherapy. All groups will be assessed at the beginning of the chemotherapy treatment, during each cycle, and at the end of the treatment (at 30 days, 3 and 6 months). Lower limb CIPN incidence, pain, body balance, sensitivity, and quality of life will be evaluated, as well as LTD use satisfaction, treatment adherence, and CIPN impacts on daily living activities. Results: This study will evaluate the effectiveness of photobiomodulation employing LTD in preventing lower limb CIPN in Brazilian breast cancer female patients undergoing neoadjuvant or adjuvant chemotherapy. The results will encompass quantitative and self-reported patient data. Conclusions: This study is expected to demonstrate a new prevention modality for this breast cancer treatment complication.